Etnomatematika “Tabut Bengkulu” Terhadap Kemampuan Berpikir Kritis Siswa Kelas IV SDN Gugus 10 Kota Bengkulu - Yuli Budi Utami (JURIDIKDAS, 2023)
This study aimed to determine the effect of the application of the model-based Discovery Learning etnomatematika toward critical thinking ability in mathematics of fourth grade students of SDN Force 10 Bengkulu City. This research is quantitative. The method used is quasy experiment with the research design matching only pretest-posttest control group design. The sampling technique using cluster random sampling. The population in this study is that SDN Force 10 fourth grade students at SDN 58 for grade control and fourth grade students at SDN 38 for the experimental class. The instrument used in this study is the critical thinking skills test sheet in the form of a description, amounting to 5 questions. Making the test twice, ie before and after the learning took place in the experimental class and control. Based on the calculation of the t-test posttest results of students, where thitung =2,10 and ttabel = 2.00. Because thitung > tabel, show that there are differences in resultsposttest between the experimental class and control class. The conclusion of this studythere is a significant effect of useetnomatematika discovery learning models based on critical thinking skills in mathematicsstudents of SDN 10 Bengkulu City Cluster.